2019
DOI: 10.1097/md.0000000000017136
|View full text |Cite
|
Sign up to set email alerts
|

Association between the DRD2 TaqIA gene polymorphism and Parkinson disease risk: an updated meta-analysis

Abstract: Background:DRD2 TaqIA polymorphism may be associated with an increased risk of developing Parkinson disease (PD). However, the individual study's results are still inconsistent.Methods:A meta-analysis of 4232 cases and 4774 controls from 14 separate studies were performed to explore the possible relationship between the DRD2 TaqIA gene polymorphism and PD. Pooled odds ratios (ORs) for the association and the corresponding 95% confidence intervals (CIs) were evaluated by a fixed-effect model.Results:The pooled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It should be also mentioned in this context that the D2R TaqIA polymorphism ( rs1800497 ) which confers a decreased receptor density was evaluated, and although the frequencies of the A1A1 and A2A2 genotypes were similar among CD patients, UC patients, and healthy controls, the CD carriers of the A2A2 genotype showed a lower risk for the development of refractory CD than A1A1 and A1A2 carriers [ 30 ]. Interestingly, a recent meta-analysis by You et al (2019) suggested a significant association between the D2R TaqIA polymorphism and PD in the recessive and additive genetic models, especially in Caucasians [ 73 ]. Pharmacologically, DA has a 10-time higher affinity for D5R than for D1R, and a 20-time higher affinity for D3R than for D2R [ 68 ], and thus can exert either immunosuppressive or pro-inflammatory roles depending on either its high or low tissue concentrations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It should be also mentioned in this context that the D2R TaqIA polymorphism ( rs1800497 ) which confers a decreased receptor density was evaluated, and although the frequencies of the A1A1 and A2A2 genotypes were similar among CD patients, UC patients, and healthy controls, the CD carriers of the A2A2 genotype showed a lower risk for the development of refractory CD than A1A1 and A1A2 carriers [ 30 ]. Interestingly, a recent meta-analysis by You et al (2019) suggested a significant association between the D2R TaqIA polymorphism and PD in the recessive and additive genetic models, especially in Caucasians [ 73 ]. Pharmacologically, DA has a 10-time higher affinity for D5R than for D1R, and a 20-time higher affinity for D3R than for D2R [ 68 ], and thus can exert either immunosuppressive or pro-inflammatory roles depending on either its high or low tissue concentrations, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…DA plays an important role in mediating the pathogenesis and treatment of PD. There are five types of dopamine receptors (DRD), namely, DRD 1-5 [ 44 ]. Among them, DRD2 has attracted considerable attention since its agonists can improve the motor symptoms of PD patients without exhibiting the side effects of movement disorders and mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Gene polymorphism: Likewise, DRD2 Taq1A (rs1800497) and DRD3 Ser9Gly (rs6208) polymorphism might be of great importance when delineating PD subtypes 15 . An association of receptor polymorphisms—as disease causing variants—has been reported for Parkinson’s disease 16 , 17 . An influence of these polymorphisms on medication response and occurrence of side effects in individual patients is part of ongoing research 18 22 .…”
Section: Introductionmentioning
confidence: 98%